(3eHGOF GdJShjb GdRQGYjs - (3CHj SYjO(B, (3GdjhfLjs ((3HZOGO(B:s (3OGQ MGeO ddfTQhGdJhRjY(B,s, 2001)
(3GdeONd dOQGSI GdJShjb GdRQGYj(B-(3NUGFU GdefJLGJ GdRQGYjI hGdMjhGfjI(B-(3GdhXGFa GdeJHGOdI(B-(3GdUfGYGJ GdZPGFjI(B-(3GdefTBJ GdJShjbjI(B-(3JhRjY GdWdH Ydi GdefJLGJ GdRQGYjI(B-(3GdJYHFI hGdJZdja(B-(3GdCSYGQ aj GdbWGY GdRQGYj(B-(3CfTWI GdJhRjY GdeGOj(B-(3GdEbQGV GdJShjbj GdRQGYj(B-(3eYdheGJ GdShb(B-(3GdSjGSGJ GdEdRGejI hGdENJjGQjI aj GdEfJGL hGdJShjbs
Keywords: (3GdGfJGL GdRQGYj(B-(3GdJShjbs; (3GdUfGYI GdZPGFjIs